2020
DOI: 10.1101/2020.02.13.948620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal antibodies to gliadin and autism spectrum disorders in offspring - A population-based case-control study in Sweden

Abstract: ObjectiveIndividuals diagnosed with autism spectrum disorders (ASD) are reported to have higher levels of antibodies directed towards gliadin, a component of wheat gluten. However, no study has examined such antibodies in etiologically-relevant periods before diagnosis. The objective of this study is to investigate if maternal levels of immunoglobulin G antibodies directed at gliadin, during pregnancy and at the time of birth, are associated with ASD in offspring. MethodsIn this population-based study set in S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This provides the child with the passive immunity against the antigens (Slifka & Amanna, 2018). A recent study conducted by Gardner et al, showed that the high level of maternal anti-gliadin antibodies protects the child against ASD (Gardner et al, 2020).…”
Section: Association Of Celiac Disease (Cd) With Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…This provides the child with the passive immunity against the antigens (Slifka & Amanna, 2018). A recent study conducted by Gardner et al, showed that the high level of maternal anti-gliadin antibodies protects the child against ASD (Gardner et al, 2020).…”
Section: Association Of Celiac Disease (Cd) With Autism Spectrum Disorder (Asd)mentioning
confidence: 99%